2019
DOI: 10.1175/jpo-d-18-0193.1
|View full text |Cite
|
Sign up to set email alerts
|

Sea Spray and Its Feedback Effects: Assessing Bulk Algorithms of Air–Sea Heat Fluxes via Direct Numerical Simulations

Abstract: Sea spray exchanging momentum, heat, and moisture is one of the major uncertainties in modeling air–sea surface heat fluxes under high wind speeds. As a result of several untested assumptions in existing models and low fidelity in the measurements, questions regarding the appropriate method for modeling the effects of spray on air–sea fluxes still exist. In this study, we implement idealized direct numerical simulations (DNS) via an Eulerian–Lagrangian model to simulate spray droplets in turbulent flows. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 36 publications
4
40
0
Order By: Relevance
“…The droplets of sea spray release water vapor to the near‐surface of the atmosphere by evaporation and loses sensible heat to the atmosphere. The studies by Richter and Stern () and Peng and Richter () discussed the role of the sea spray on the enthalpy flux under the strong wind (typhoon wind).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The droplets of sea spray release water vapor to the near‐surface of the atmosphere by evaporation and loses sensible heat to the atmosphere. The studies by Richter and Stern () and Peng and Richter () discussed the role of the sea spray on the enthalpy flux under the strong wind (typhoon wind).…”
Section: Methodsmentioning
confidence: 99%
“…The logarithmic formula of wind profile was modified by introducing the influence of sea spray droplets on the dynamic sea surface roughness length in the strong wind conditions (Makin, ). While a few studies (Wu et al, ; Garg et al, ) reported existing uncertainty in the impact of sea spray on the intensity of the storms, a recent study by Peng and Richter () stated that the contribution of sea spray to the enthalpy flux in hurricane conditions might be greatly overestimated. Hence, the role of sea spray on storms is not properly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the LES considered here, the simulated Lagrangian sea spray aerosol particles maintain a constant size, meaning that hygroscopicity and aerosol swell are not considered (Winkler, 1988). The changing atmospheric conditions due to the diurnal cycle have been neglected, as have momentum and energy exchange between the aerosol particles and the air (e.g., neglecting the effects of spray modifying heat and moisture in the surface layer Peng & Richter, 2019). Lastly, the LES assumes a flat surface with a prescribed aerodynamic roughness length, although in the open ocean the moving surface waves may play a substantial role in the transport and fate of sea spray aerosol particles (Richter et al, 2019).…”
Section: Numerical Methodologymentioning
confidence: 99%
“…The three studies Peng andRichter (2017, 2019) and Peng and Richter (2020) used direct numerical simulations (DNSs) with a Lagrangian-Eulerian framework and focused on whether common assumptions made by many bulk flux algorithms, including neglecting interactions between spray drops and neglecting feedbacks between spray fluxes and the ambient conditions, are valid assumptions. The 3D domains used throughout these experiments were all on the order of 0.01 m 3 , had a no slip lower boundary condition, and a stress-free upper boundary condition.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Improving the representation of air-sea enthalpy and momentum fluxes in particular is key to improving intensity forecast accuracy. Since sea spray has been shown to mediate a significant percentage of the total enthalpy and momentum fluxes in TCs (Andreas and Emanuel 2001, hereafter AE1;Andreas 2004;Zhao et al 2006;Andreas 2010;Richter and Stern 2014;Mueller and Veron 2014b;Troitskaya et al 2018b;Peng and Richter 2017, 2020, bulk parameterizations have begun to incorporate the microphysics associated with sea spray-mediated fluxes. In particular, many of the investigations specifically focus on the way sea spray affects the bulk surface exchange coefficients for enthalpy C K and momentum C D .…”
Section: Introductionmentioning
confidence: 99%